Genomic Analysis Uncovers Immune Microenvironment Characteristics and Drug Sensitivity of Ferroptosis in Breast Cancer Brain Metastasis - Zhu, Lei; Chen, Mu; Huang, Bingsong; Zhang, Tao; Chen, Kui; Lian, Hao; Liu, Min; Zhao, Kaijun; Pang, Ying; Zhang, Jing; Li, Qinchuan; Zhong, Chunlong (Frontiers in Genetics, 2022)
Background The role of ferroptosis in breast cancer brain metastasis (BCBM) is unclear. This study aimed to explore the ferroptosis-related genes (FRG) relations with the tumor microenvironment, as well as evaluate their values in predicting survival and drug sensitivity in patients with BCBM. Materials and Methods Genes expression and clinical data were downloaded from Gene Expression Omnibus (GEO). Univariate and multivariate Cox regression analyses were performed to explore the independent prognostic factors. Consensus cluster principal component analysis (PCA) was used to establish the ferroptosis score. Immunological signatures were analyzed by the single-sample gene set enrichment analysis (ssGSEA). Drug sensitivity was evaluated through the estimated half-maximal inhibitory concentration (IC50). Finally, results were validated in external cohorts. Results Fourteen significantly different FRG were identified between breast cancer (BC) and BCBM tissues. Survival analysis demonstrated HMOX1, PEBP1, KEAP1 and LPCAT3 were significantly associated with overall survival (OS) and relapse-free survival (RFS) (P< 0.05). High ferroptosis was correlated with iron ion homeostasis, iron metabolism, higher stromal cells and immune cells scores. Patients with high- and low-ferroptosis scores were characterized by different drug sensitivities. Following external validation, the ferroptosis had distinct expression profiles between the BC and BCBM, and could serve as biomarkers for OS and drug response. Conclusions Our findings suggested that ferroptosis may be involved in the process of BCBM, and ferroptosis could serve as prognostic biomarkers. Evaluation of ferroptosis may deepen our understanding about the tumor microenvironment, and could help clinicians to make individualized therapy.